Farmers' willingness to adopt good agricultural practices the case of smallholder vegetable farmers in Davao City - Boborol, Honey Jane B.; Shuck, Vlademir A. (2018)
Good Agricultural Practices (GAP) is a way of farming that responds to the increasing demand of consumers for food safety. GAP adoption in the Philippines is still in its infancy stage. In Davao City, there is no GAP certified smallholder farms yet. This study assessed Davao City smallholder vegetable farmers? knowledge and awareness on GAP, their willingness to adopt GAP and the factors affecting their decision. The study was conducted in three districts of Davao City ? Marilog, Toril and Tugbok where most number of farmers are located. Likert scale was used to assess farmers? knowledge on GAP farming. Binary logistic regression was used to analyze the factors that affects farmers? willingness to adopt GAP farming. Results show that only 47.65% of vegetables farmers have heard of GAP and only 33.63% of them are well aware of the different GAP practices that were recommended by Philippine National Standard. Also, results show that training and land ownership have positive and significant effect on farmers? willingness to adopt GAP. These variables have a marginal effect of 4% and 14% respectively. Training has a 24% correlation with GAP adoption while land ownership has 25%. In order to efficiently increase GAP adoptation in vegetable farmers, it is recommended that the government provide more agricultural related trainings and target farmers who own their farm land.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2018